Association between the frequency of television watching and overweight and obesity among women of reproductive age in Nepal: Analysis of data from the Nepal Demographic and Health Survey 2016 - Gupta, Rajat Das; Haider, Shams Shabab; Hashan, Mohammad Rashidul; Hasan, Mehedi; Sutradhar, Ipsita; Sajal, Ibrahim Hossain; Joshi, Hemraj; Haider, Mohammad Rifat; Sarker, Malabika (PLOS ONE, 2022)
This article was published in The Plos One [© 2020 Das Gupta et al. This is an open access article distributed under the terms of the Creative Commons Attribution License.] and the definite version is available at: https://doi.org/10.1371/journal.pone.0228862 The Journal's website is at: https://journals.plos.org/plosone/article?id=10.1371/journal.pone.0228862